Dually Ordered Porous TiO2‐rGO Composites with Controllable Light Absorption Properties for Efficient Solar Energy Conversion. Issue 4 (22nd November 2016) - Yang, Yu; Jin, Quan; Mao, Dan; Qi, Jian; Wei, Yanze; Yu, Ranbo; Li, Anran; Li, Shuzhou; Zhao, Huijun; Ma, Yanwen; Wang, Lianhui; Hu, Wenping; et al.
Abstract : Quadruple‐layered TiO2 films with controllable macropore size are prepared via a confinement self‐assembly method. The inverse opal structure with ordered mesoporous (IOM) presents unique light reflection and scattering ability with different wavelengths. Cyan light (400–600 nm) is reflected and scattered by IOM‐195, which is in accord with N719 absorption spectra. By manipulating the macropore size, different light responses are obtained.